2023
DOI: 10.3390/ijerph20065014
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties and Validation of the Italian Version of Ages & Stages Questionnaires Third Edition

Abstract: Objectives: The Ages & Stages Questionnaires Third Version (ASQ-3) identifies the risk of developmental delay in children aged 1 to 66 months. The aim of this study was to determine a reliable and valid instrument for the Italian population to enable the screening of children’s development. Methods: Data from 2278 Italian children (age range: 1–66 months) were used to evaluate item discrimination power using the corrected item-total correlation. Internal consistency was analyzed by Cronbach’s alpha scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Although the reliability between items was lower than that reported in the US and in a previous study conducted in Chile with national representation and using a paper‐pencil modality (Armijo et al, 2015; Squires & Bricker, 2009), Cronbach's alpha between items and total score was significant. Studies performed in different countries reported variable results, depending on the heterogeneity of the sample (Helms et al, 2006), which might explain the differences between results in the current sample with WB‐ASQ‐3 versus the previous study carried out in a national sample, in the original validation in the USA, at Daycare centers in Brazil or Italy (Armijo et al, 2015; Filgueiras et al, 2013; Manti et al, 2023; Squires & Bricker, 2009), which is different from more homogenous samples (Charafeddine et al, 2013; Lopes et al, 2015; Schonhaut et al, 2019). In a systematic review, Velikonja y cols reported that the reliability of the ASQ was generally ‘positive’ for the original versions of the ASQ‐3, compared to the translated/adapted questionnaires, for more culturally specific domains in particular (Velikonja et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although the reliability between items was lower than that reported in the US and in a previous study conducted in Chile with national representation and using a paper‐pencil modality (Armijo et al, 2015; Squires & Bricker, 2009), Cronbach's alpha between items and total score was significant. Studies performed in different countries reported variable results, depending on the heterogeneity of the sample (Helms et al, 2006), which might explain the differences between results in the current sample with WB‐ASQ‐3 versus the previous study carried out in a national sample, in the original validation in the USA, at Daycare centers in Brazil or Italy (Armijo et al, 2015; Filgueiras et al, 2013; Manti et al, 2023; Squires & Bricker, 2009), which is different from more homogenous samples (Charafeddine et al, 2013; Lopes et al, 2015; Schonhaut et al, 2019). In a systematic review, Velikonja y cols reported that the reliability of the ASQ was generally ‘positive’ for the original versions of the ASQ‐3, compared to the translated/adapted questionnaires, for more culturally specific domains in particular (Velikonja et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…Given that the participation in screening programs was voluntary, a certain amount of non‐adherence was to be expected; in this study, it stood out that 86% of enrolled children answered at least one development assessment, which is above the participation reported in other survey studies (Janson, 2003) and it was certainly encouraged by the web‐based modality. In addition, the low proportion of incorrectly fulfilled questionnaires indirectly confirmed that the ASQ‐3 was relatively easy to complete (Manti et al, 2023). Although we do not take a gold standard test as a reference, the dimensions analysed allow us to conclude that the instrument is reliable and feasible to apply.…”
Section: Discussionmentioning
confidence: 94%
“…We assessed children's cognitive development at 18 months using the validated tool ASQ-3 [25,26]. The ASQ-3 is a screening tool reported by parents, which assesses the children's cognitive development across five domains: communication, gross motor, fine motor, problem solving, and personal-social.…”
Section: Assessment Of Children's Cognitive Developmentmentioning
confidence: 99%
“…Based on the ASQ-3 cutoffs, we categorized each domain into three groups: development on schedule (DS) (scores above the cut-off), requiring learning activities and monitoring (RLAM) (scores close to the cut-off), further assessment required with a professional (FARP) (scores below the cut-off) [28,29]. Communication scores were categorized as: DS (30-60); RLAM (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29); FARP (0-14) [28,29]. Gross motor scores were categorized as: DS (46-60); RLAM (36)(37)(38)(39)(40)(41)(42)(43)(44)(45); FARP (0-35).…”
Section: Assessment Of Children's Cognitive Developmentmentioning
confidence: 99%
See 1 more Smart Citation